Post‐illumination transient O2‐uptake is driven by photorespiration in tobacco leaves. Issue 2 (22nd October 2015) - Sejima, Takehiro; Hanawa, Hitomi; Shimakawa, Ginga; Takagi, Daisuke; Suzuki, Yuji; Fukayama, Hiroshi; Makino, Amane; Miyake, Chikahiro
Abstract : This study aims to elucidate the molecular mechanism for the transient increase in the O2 ‐uptake rate in tobacco ( Nicotiana tabacum cv Xanthi) leaves after turning off actinic lights (ALs). The photosynthetic O2 evolution rate reaches a maximum shortly after the onset of illumination with ALs and then decreases to zero in atmospheric CO2 /O2 conditions. After turning off the ALs, tobacco leaves show a transient increase in the O2 ‐uptake rate, the post‐illumination transient O2 ‐uptake, and thereafter, the O2 ‐uptake rate decreases to the level of the dark‐respiration rate. Photosynthetic linear electron flow, evaluated as the quantum yield of photosystem II [Y(II)], maintained a steady‐state value distinct from the photosynthetic O2 ‐evolution rate. In high‐[CO2 ] conditions, the photosynthetic O2 ‐evolution rate and Y(II) showed a parallel behavior, and the post‐illumination transient O2 ‐uptake was suppressed. On the other hand, in maize leaves (a C4 plant), even in atmospheric CO2 /O2 conditions, Y(II) paralleled the photosynthetic O2 ‐evolution rate and the post‐illumination transient O2 ‐uptake was suppressed. Hypothesizing that the post‐illumination transient O2 ‐uptake is driven by C3 plant photorespiration in tobacco leaves, we calculated both the ribulose 1, 5‐bisphosphate carboxylase‐ and oxygenase‐rates (Vc and Vo) from photosynthetic O2 ‐evolution and the post‐illumination transient O2 ‐uptake rates. These values corresponded to those estimated from simultaneous chlorophyll fluorescence/O2 ‐exchange analysis. Furthermore, the H + ‐consumption rate for ATP synthesis in both photosynthesis and photorespiration, calculated from both Vc and Vo that were estimated from chlorophyll fluorescence/CO2 ‐exchange analysis, showed a positive linear relationship with the dissipation rate of the electrochromic shift signal. Thus, these findings support our hypothesis.